An Analysis of the Seventh-Grade Science Textbook in Terms of Science, Engineering, and Entrepreneurship Applications - Kadriye KAYACAN; Münevver ÖZLÜLECİ (Anı Publishing, 2021)
The purpose of the present study is to analyse the secondary school 7th-grade science textbook in terms of science, engineering, and entrepreneurship applications, an area of practice emphasised in the curriculum restructured in 2018. For this purpose, the document analysis method, one of the qualitative research methods, was employed in the study. The research data source consists of 6 project design activities in the 7th-grade science textbook taught in the 2018-2019 academic year. The project design activities were analysed by content analysis. Analysis findings found coordination between the attainment of some curriculum units and the instructions in the textbook failed to be achieved. Deficiencies in terms of material, time, and cost according to science, engineering, and entrepreneurship evaluation criteria in the project design sections were also found. It was concluded that the link between the curriculum and textbook should be improved in some units following the science assessment criteria.